למלכה אין בית, למלך אין כתר: קריסתן של צורות ספרותיות קדומות ביצירת ש"י עגנון ולאה גולדברג - מרינברג מליקובסקי, איתי (מכאן, 2022)
To what extent can ancient literary forms fulfill their role in a world where the good old order that enabled and is reflected in them has disintegrated? This broad question illuminates the relationship between Modem and pre-modem Hebrew literature. Distinctions between conventional cultural images of the sacred and the secular that have been intensively criticized and conceptualized in the last decade are only part of the question. Even if there is a basis for the claim that Modem Hebrew literature has not turned its back on profound religious streams that originated in pre-modem literature, it is hard to deny that Modem Hebrew literature faces a world that is completely different from the one that shaped its predecessors. In this article, the author seeks to examine the metamorphoses of two ancient forms - the parable and the fairy tale - as they are treated in two specific works by S.Y. Agnon and Leah Goldberg. These forms, which have a clear affinity to mythical pre-modem modes of thought and have been constantly present in Hebrew and non-Hebrew literature for generations, have a hard time making their way into the new world as the power they used to have in terms of the ability to make sense of reality is impossibly tested under different conditions. Through a close reading of Agnon’s A Guest for a Night and Goldberg’s A Tale of Three Nuts, the author demonstrates how deep transformations in the old European order, i.e. the decline of the monarchy and the growth of the modem nation state, the rise of the bourgeoisie and accelerated secularization, and the horrors of the world wars and concomitant devastation of Jewish life, gave birth to and even necessitated a reflexive observation of traditional literary forms. Thus, ultimately, both Agnon and Goldberg announce - albeit in a whisper - the demise of these forms and their incapacity to deal with the new world.